PENGEMBANGAN DAYA TARIK OBJEK WISATA OI FANDA KECAMATAN AMBALAWI KABUPATEN BIMA - Jaenab, Jaenab; Huda, Nurul; Fiqkin, Muhammad Ahlul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The importance of developing tourism that can support the regional economy in ambalawi Regency is Oi Fanda which is located in ujung harapan hamlet. Nipa Village, ambalawi District, Bima regency. This activity involved real work lecture students from Nipa Village, Ambalwi district, who were accompanied by assistant lecturers from the manegement study program, Pokdarwis and the community of the Ujung Harapan hamlet. Oi Fanda has clean white sand a stretch of coconut which adds to the beauty of a tourist attraction that is currently viral on social media. Many residents from the city of Bima and other area also deliberately visited Oi Fanda. The development is carried out by making directions to tourist attraction locationt, welcome boards, photo spot, lounge chairs, swings, promotions and publications on social media. The development of the Oi Fanda tourist attraction will have an impact on the arrival of visitors to the Oi Fanda tourist attraction, which will increase the income of the Nipa village community. The tourism sector is a sector that has the potential to be developed as a source of regional insight. The development of tourism depends on the visits that come to visit the place. The increase in the number of visits that occur is a reflection of the continued development of tourism to maintain and increase the number of tourist visits.